2019
DOI: 10.3928/01477447-20190211-01
|View full text |Cite
|
Sign up to set email alerts
|

Trends and Risk Factors in Orthopedic Lawsuits: Analysis of a National Legal Database

Abstract: Orthopedic surgeons frequently encounter medical malpractice claims. The purpose of this study was to assess trends and risk factors in lawsuits brought against orthopedic surgeons using a national legal database. A legal research service was used to search publicly available settlement and verdict reports between 1988 and 2013 by terms “orthopaedic or orthopedic” and “malpractice.” Temporal trends were evaluated, and logistic regression was used to identify independent risk factors for case outcomes. A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 32 publications
1
17
0
1
Order By: Relevance
“… 2 Of cases that go to court, 54-75% end favorably for the surgeon/defense ( Table 2 ). 5 - 8 , 10 , 14 , 18 Makhni et al 14 noted that 75% of malpractice suits filed between 2010 and 2014 ended in favor of the defendant. In a separate review of cases ending in settlement or a jury verdict, Daniels et al 9 reported that 54.2% of cases ruled in favor of the defense while 26.1% of cases resulted in plaintiffs’ verdicts and 19.6% ended in a settlement.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 2 Of cases that go to court, 54-75% end favorably for the surgeon/defense ( Table 2 ). 5 - 8 , 10 , 14 , 18 Makhni et al 14 noted that 75% of malpractice suits filed between 2010 and 2014 ended in favor of the defendant. In a separate review of cases ending in settlement or a jury verdict, Daniels et al 9 reported that 54.2% of cases ruled in favor of the defense while 26.1% of cases resulted in plaintiffs’ verdicts and 19.6% ended in a settlement.…”
Section: Resultsmentioning
confidence: 99%
“…2 Of cases that go to court, 54-75% end favorably for the surgeon/defense (Table 2). 5-8,10,14, 18 Makhni et al 14 While most cases that progress to a jury verdict end favorably for the defense, specific case characteristics can influence results. Agarwal et al 10 noted significant increases in plaintiffs' verdicts in litigation that cited failure to treat (P ¼ .025), patient death (P ¼ .04), or cases involving emergent surgery (P ¼ .002).…”
Section: Outcomes Of Litigationmentioning
confidence: 99%
“…If this trend negatively affects their reimbursements, then they may be forced out of the market. On the other hand, increasing malpractice litigation 9 against orthopaedic surgeons over the past 3 decades has caused rising malpractice insurance costs, which may be burdensome to smaller-sized practices. A general perception that patients with Medicaid status will be more likely to pursue malpractice lawsuits exists.…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion is also shared in the 2014 report of the French observatory of medical risks which concludes that 60% of disputes relate to a surgical procedure. The reason orthopaedics comes to the top of the ranking is mainly because of the number of surgical procedures it carries out, which far exceeds other specialities [13].…”
Section: Discussionmentioning
confidence: 99%